The possibilities of virtual reality-goggles within the teaching and learning of History (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Currently the educational system is experiencing a process in which different teaching and learning methods are being used in conjunction with several forms of technology with the aim of improving the educational process. This is only a natural aspect of the educational process when looking at it within a larger societal sphere. When placing focus on subjects - specifically History – it should be noted that History as subject requires the incorporation of more modern technology in order to move away from the traditional method of chalk and talk History instruction. There are various teaching and learning aids like interactive whiteboards and data projectors but they are however not the latest forms of technology that can be used as a pedagogy tool that place is reserved for Virtual Reality (VR) and the goggles that accompanies it. Virtual Reality is a computer simulated environment – cyberspace/ augmented reality – with which the technology user can interact. Within this cyberspace the user focuses on virtual sights and virtual sounds in an attempt to create immersive experiences through the application of technologies like VR-Goggles which are also known as Head Mounted Displays (HMD’s). The aim of this article is to introduce Virtual Reality and the accompanying goggles to History educators and look at possibilities on how it can be utilised.
Keywords: Virtual Reality (VR); VR-Goggles; HMD’s; TPACK; Technology; History teaching and learning